Tipping the scales: Evolution of the allometric slope independent of average trait size. (8th February 2016) - Stillwell, R. Craig; Shingleton, Alexander W.; Dworkin, Ian; Frankino, W. Anthony
Abstract : The scaling of body parts is central to the expression of morphology across body sizes and to the generation of morphological diversity within and among species. Although patterns of scaling‐relationship evolution have been well documented for over one hundred years, little is known regarding how selection acts to generate these patterns. In part, this is because it is unclear the extent to which the elements of log‐linear scaling relationships—the intercept or mean trait size and the slope—can evolve independently. Here, using the wing–body size scaling relationship in Drosophila melanogaster as an empirical model, we use artificial selection to demonstrate that the slope of a morphological scaling relationship between an organ (the wing) and body size can evolve independently of mean organ or body size. We discuss our findings in the context of how selection likely operates on morphological scaling relationships in nature, the developmental basis for evolved changes in scaling, and the general approach of using individual‐based selection experiments to study the expression and evolution of morphological scaling.